2012
DOI: 10.1002/hipo.22018
|View full text |Cite
|
Sign up to set email alerts
|

Ensembles of human MTL neurons “jump back in time” in response to a repeated stimulus

Abstract: Episodic memory, which depends critically on the integrity of the medial temporal lobe (MTL), has been described as “mental time travel” in which the rememberer “jumps back in time.” The neural mechanism underlying this ability remains elusive. Mathematical and computational models of performance in episodic memory tasks provide a specific hypothesis regarding the computation that supports such a jump back in time. The models suggest that a representation of temporal context, a representation that changes grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 87 publications
(119 reference statements)
7
92
0
Order By: Relevance
“…By comparing reinstatement during correct and incorrect retrieval, our findings build upon recent evidence that trial-specific reinstatement of this neural representation of temporal context occurs during successful retrieval (20,21). If successful retrieval is associated with the recovery of a temporal context representation, then we would expect to find a graded decrease in reinstatement as retrieval periods were paired with encoding periods separated by longer time intervals in both the forward and backward direction (6,8,21). Consistent with this prediction, our data demonstrate a contiguity effect for correct trials within lists.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…By comparing reinstatement during correct and incorrect retrieval, our findings build upon recent evidence that trial-specific reinstatement of this neural representation of temporal context occurs during successful retrieval (20,21). If successful retrieval is associated with the recovery of a temporal context representation, then we would expect to find a graded decrease in reinstatement as retrieval periods were paired with encoding periods separated by longer time intervals in both the forward and backward direction (6,8,21). Consistent with this prediction, our data demonstrate a contiguity effect for correct trials within lists.…”
Section: Discussionsupporting
confidence: 53%
“…However, because retrieval in this study was unconstrained, one possibility is that the observed reinstatement was a consequence, rather than a cause, of retrieval contiguity. Spiking activity in the medial temporal lobe has also been shown to reinstate activity present during encoding (21,22). However, it is unknown how the temporal dynamics of neural activity distinguish reinstatement between correct and incorrect memory retrieval across broader cortical regions.…”
mentioning
confidence: 99%
“…Memory formation is crucial for learning from novel relevant experiences (Rutishauser, Ross, Mamelak, & Schuman, 2010), and iEEG evidence has reliably illustrated the importance of amygdala neuronal activity in encoding, recognition and recall accuracy of objects and events ( c o r t e x 6 0 ( 2 0 1 4 ) 1 0 e3 3 Heit, Smith, & Halgren, 1988;Howard, Viskontas, Shankar, & Fried, 2012;Kreiman, Koch, & Fried, 2000b;Paz et al, 2010;Quian Quiroga, Kraskov, Koch, & Fried, 2009;Quiroga, Mukamel, Isham, Malach, & Fried, 2008, Quiroga, Reddy, Kreiman, Koch, & Fried, 2005Rutishauser et al, 2010). Importantly, this occurs independently of sensory modality (Quian Quiroga et al, 2009).…”
Section: Memory Formation and Retrievalmentioning
confidence: 98%
“…For instance, categories (e.g., animals) and specific objects (e.g., individuals) are shown to yield selective amygdala neuronal FR at encoding and recognition irrespective of presentation context and angular configurations (Gelbard-Sagiv et al, 2008;Kreiman, Fried, & Koch, 2002;Mormann et al, 2011;Quian Quiroga et al, 2009;Quiroga et al, 2005). Consequently, the amygdala may be removed from encoding contextual aspects relevant to the experienced stimulus, including temporal relationships of events and objects (Howard et al, 2012;Paz et al, 2010), spatial location of the respective stimulus (Rutishauser, Mamelak, & Schuman, 2006, Rutishauser, Schuman, & Mamelak, 2008, and even affectively neutral associative relationships (Cameron et al, 2001). Single-neuron studies by Howard et al (2012) and Paz et al (2010) both failed to show significant amygdala neural responding that would be indicative of temporal order processing of experienced events.…”
Section: Memory Formation and Retrievalmentioning
confidence: 99%
See 1 more Smart Citation